Analysis Of Surah Al-Ashr In Perspective Context & Intertext - Asadi Siregar, Akram; Jannah, Savinatul; Susiawati, Wati (Rayah Al-Islam, 2024)
This research aims to find out how the verses in surah Al-ashr and the verses in This research aims to find out how the verses in surah Al-ashr with other verses of the Qur'an interpret each other (intertext) and how the context behind the verses in surah Al-ashr is interpreted. This research aims to find out how the verses in surah Al-ashr and other verses of the Qur'an interpret each other (intertext) and how the context behind the revelation of the verse. This research using descriptive qualitative. The conclusion of this study found that surah al-Ashr verse 3 explains the exclusion of those who are losers, namely those who believe, do righteous deeds, and those who do good deeds. the exception of those who are losers, namely those who believe, do righteous deeds, advise each other in righteousness and patience. And each of the words Faith, Good deeds and Patience has a Context and Intertext. Patience has Context and Intertext in other verses in the Qur'an.